An overview of Arzani khaishki Zamand as Imam of Pashto Alifnama - Qadir, Shukria (sourcecoder, 2022)
Alif nama or See Harfi is a well-known genre of poetry. This genre belongs to Persian literature and came from Persian to other Eastern languages. Subjects of this genre are mostly related to ethics or mysticism. In case of Pashto literature also this genre came from Persian literature and achieved such a status that now it is considered as genre of Pashto literature in its own place. In Pashto poetry, many poets have tried their hand at this genre. They have been created many wonderful Alif namas, which are the great examples and rich sources of knowledge, mysticism and Sufism. This article discusses the Alif namas of Mula Arzani khwaishke, the first Pashto poet of Alif nama and sheds light on his thoughts and art.